Toddler feeding, WASH conditions, and clinical complaints during the 2024 flash flood disaster in Jorong Galuang, Sungai Pua District, Agam Regency, West Sumatra - Asbi Shinta; Rachmawati Masnadi Nice; Mayetti (E3S Web of Conferences)
This study focuses on the impact of flash floods in Jorong Galuang, Sungai Pua, particularly on toddler nutrition, water, sanitation, hygiene (WASH), and clinical health. A qualitative study conducted through interviews and direct observation, data were collected from mothers of toddlers, health officers, midwives, and NGO representatives AIMI. Despite the absence of dedicated MPASI kitchens during the disaster, toddlers did not experience significant difficulties with feeding due to aid from NGOs and the availability of undamaged kitchens in some homes. Water access remained sufficient through local springs and additional supplies from the PMI ( Palang Merah Indonesia), although hygiene practices, particularly handwashing, were inadequate. Clinical complaints among toddlers were predominantly respiratory issues, including coughs and colds, with a few cases of diarrhea reported.